Penerapan Sistem Manajemen Mutu ISO 9001:2015 dalam Mendukung dan Menunjang Pemasaran terhadap Perhotelan: Narative Literature Review - Merici, Elfriyani Angela; Hermawan, Dede (AGUSPATI RESEARCH INSTITUTA, 2024)
This study aims to determine the application of quality management in hotels. The data used in this study aims to describe the forms of management responsibility, resource management, product realization processes, measurement, analysis and improvement in hotels. This type of research is descriptive qualitative. The data obtained will be tested for its validity using source and technique triangulation, in which the researcher compares the data obtained from the informants and the observations to check the correctness of the data. The results of the study show that the quality management system in hotels has been formally implemented but the factual implementation has not fully proceeded according to procedures. Therefore, the organization needs to establish a special quality team and regularly remind employees about the importance of following the rules that have been set. Keywords-Quality Management System, Management Responsibilities, Resource Management, Product Realization, Measurement, Analysis and Improvement